Mathematical Approaches to Biological Systems: Networks, Oscillations, and Collective Motions - Ohira, Toru (Springer, 2015)
This book presents the most recent mathematical approaches to the growing research area of networks, oscillations, and collective motions in the context of biological systems. Bringing together the results of multiple studies of different biological systems, this book sheds light on the relations among these research themes.